Comparison of degranulation of easily mobilizable intracellular granules by human phagocytes in healthy subjects and patients with infectious diseases - Nuutila, Jari; Jalava-Karvinen, Päivi; Hohenthal, Ulla; Laitinen, Iina; Kotilainen, Pirkko; Rajamäki, Allan; Nikoskelainen, Jukka; Lilius, Esa-Matti (Human immunology, 2009)
The aim of this study was to compare degranulation of easily mobilizable secretory vesicles (SVs) or secretory vesicle-like granules (SVLGs) in neutrophils, monocytes, and eosinophils of healthy controls ( n = 60) and febrile patients with microbiologically confirmed or clinically diagnosed bacterial ( n = 89) and viral ( n = 46) infections. For this purpose, flow cytometric immunophenotyping of isolated phagocytes was performed using monoclonal antibodies against the phagocytosis receptors CR1 (CD35) and CR3 (CD11b) that are predominantly stored in the SVs of resting neutrophils. Similar to neutrophils, monocytes contain easily mobilizable SVLGs that constitute the main intracellular reservoir of CD35 and CD11b. In both neutrophils and monocytes, activation mechanisms leading to degranulation of SV and SVLG appeared dependent on both intra- and extracellular calcium levels. The kinetics of degranulation of SVLGs in control monocytes was significantly faster than that of SVs of control neutrophils. We conclude that phagocytes in patients with bacterial infections can be arranged in order of decreasing magnitude of SV or SVLG degranulation as follows (from left to right): neutrophils > monocytes >> eosinophils. However, in viral infections, the corresponding degranulation order is monocytes > neutrophils ≈ eosinophils.